NSun2 Deficiency Protects Endothelium From Inflammation via mRNA Methylation of ICAM-1. Issue 6 (18th March 2016) - Luo, Yuhong; Feng, Juan; Xu, Qingbo; Wang, Wengong; Wang, Xian
Abstract : Rationale : Vascular endothelial inflammation, including the expression of intercellular adhesion molecule 1 (ICAM-1), is a key event in vascular diseases. However, the mechanisms underlying the regulation of ICAM-1 are largely unknown. Objective : To investigate the mechanisms on the regulation of ICAM-1 by NOP2/Sun domain family, member 2 (NSun2)-mediated mRNA methylation and the impact of NSun2–ICAM-1 regulatory process in vascular inflammation and allograft arteriosclerosis. Methods and Results : By using in vitro, in cells, and in vivo methylation assays, we showed that the tRNA methyltransferase NSun2 methylated the ICAM-1 mRNA. Methylation by NSun2 promoted the translation of ICAM-1, thereby increasing the adhesion of leukocytes to endothelial cells. Tumor necrosis factor-α or homocysteine activated the methyltransferase activity of NSun2 by repressing the phosphorylation of NSun2 by Aurora-B. The levels of ICAM-1 induction and of leukocyte adhesion to vascular endothelium observed with homocysteine treatment in wild-type rats were markedly decreased in NSun2 −/− rats. In a rat model of aortic allograft, the lack of donor NSun2 impaired the formation of allograft arteriosclerosis. Conclusions : NSun2 upregulates the expression of ICAM-1 by methylating ICAM-1 mRNA. This regulatory process impacts on vascular inflammation and allograft arteriosclerosis. Abstract : Supplemental Digital Content is available in the text.